Study on Thermal and Mechanical Properties of SBS/PCL Based Thermo-Responsive Shape Memory Polymer Nanocomposite Actuator. (2020) - Gopinath, Sithara; Radhakrishnan Nair, P.; Mathew, Suresh
Abstract: The present paper study the thermal, electrical and shape memory behavior of Polystyrene-block-Polybutadiene-block-Polystyrene (SBS) and Polycaprolactone (PCL) blend reinforced with Carbon nanofibers (CNF). Here SBS acts as an elastomer, PCL behaves as switch polymer and CNF is used as a conductive filler which facilitates shape memory polymer Nano Composite (SMPNC). The immiscibility between the microstructures is demonstrated in DSC results. Characterization techniques such as, TGA, Shape memory test etc. were also conducted. The results show that this is an optimized SMP system with good shape recovery and fixing performances.